A Design of Coreless Permanent Magnet Axial Flux Generator for Low Speed Wind Turbine - Abdul Aziz Yusuf; M. Irfan; M. Fattahur Razzaq (IAES Indonesia Section, 2018)
Most of the available generators in the market are a high speed induction generator which requires high rotational speed and electricity to generate a magnetic field. However, there are very few low-speed generators that exist in the market that available for small energy resources. This paper aims to design and simulate a Coreless Permanent Magnet Axial Flux Generator (PMAFG) for low speed wind turbine. An axial flux generator was designed to have a low speed rotation using a permanent magnet of the type Neodymium Iron Boron (NdFeB). The model was examined with excel to data analyzed. Coreless PMAFG is a generator that is enabled to turn on energy at low speeds. The chosen model was Double Rotor - Single Stator (12 Slots 8 Poles) using Infolytica Magnet software. Finite Element Method (FEM) was employed to analyze the phenomena of the magnetic flux. The test was simulated using static rotation method, which rotated every 3 degrees at 350 rpm with 100 turns and 10, 30, 50, 80 and 100 Ohm of load variations. Compare to the calculation of the design, results of the simulation in terms of voltage, current, power and efficiency had been met with only very small errors